Effects of supply chain practices, integration and complexity on performance quality of tier one suppliers in the Malaysian automobile industry - Idris, Safuan (2015)
The primary research objectives of the study are to investigate the degree, nature and impact of the Supply Chain Management practices towards quality performance, to investigate the extent of the Supply Chain Integration’s role in affecting the relationship between Supply Chain Management practices and quality performance, and to investigate the extent of the Supply Chain Complexity influencing the relationship between Supply Chain Management practices and Supply Chain Integration. As a whole this study is on the Supply Chain Management practices moderated by Supply Chain Complexity, affecting Supply Chain Integration which in turn affects quality performance. This study mainly focuses on the tier 1 vendors in the Malaysian automotive industry sector which plays an important role in the Malaysian economy. This is evident with the launch of the National Automotive Policy (NAP) on 24th January 2014. Careful and thorough steps were taken to develop the research instruments and perform the relevant statistical analysis in achieving the research objectives. The primary data collection was through a questionnaire survey. All hypotheses were tested by submitting the model to structural equation modelling after conducting the confirmatory factor analysis (CFA) to address the validity and reliability of the construct. The results indicated that the Supply Chain Management practices in tier 1 vendors in the Malaysian automotive industry have an impact on the quality performance. There are also evidences that this impact is mediated by Supply Chain Integration. Results also reveal that Supply Chain Complexity moderates the effect of Supply Chain Management practices on Supply Chain Integration. This study exposes three important findings which are: 1) as a second order construct, internal and external focus Supply Chain Management practices have an impact on quality performance in the tier 1 vendor of the automotive industry in Malaysia, 2) the supply Chain Integration affect the impact of Supply Chain Management practices on quality performance in the tier 1 vendor of the automotive industry in Malaysia, and 3) the tier 1 vendors need to pay attention on Supply Chain Complexity because it influences the effects of Supply Chain Management practices on Supply Chain Integration. The present study has integrated the input from the automotive specific quality management standard ISO/TS 16946, and review of previous works and relevant theoretical foundation. The study also serves as among the first few attempts to bridge the gap in the literature by providing empirical support that is significant to the body of knowledge.